World politics, human rights, and international law - Boyle, Francis Anthony (Lexington Books, 2021)
Denouncing Obama at the University of Illinois -- Civil resistance against the Trump administration! -- Resisting Trump's ICEstapo! -- Resisting Trump's lawyer at the University of Illinois College of Law -- Resisting Trump's Consigliere Dershowitz at the University of Illinois -- Resisting Trump's CIA director bloody Gina Haspel -- Trump targets Iran! -- Hillary Clinton is a psychopath and a war criminal -- International Criminal Court : the white man's court -- Trump's lethal decision on Jerusalem -- Stopping Zionist genocide against the Palestinians : the boycott, divestment, and sanctions (BDS) Campaign -- The criminality of nuclear deterrence today -- U.S. biowarfare programs have 13,000 death scientists hard at work -- The mass rape of the Bosnian women was genocide! -- What is the future for Bosnia and Herzegovina? -- Interview with Francis Boyle on Bosnian "peace" [sic!] negotiations -- Stopping genocide by the government of Sri Lanka against the Tamils -- The native Hawaiian independence movement -- Amnesty international is a white racist Western colonial imperialist tool -- Conclusion. Implications of the worldwide COVID-19 pandemic for world politics, human rights, and international law.